Collaborative Tagging: Providing User Created Organizational Structure for Web 2.0 - Banek Zorica, Mihaela; Špiranec, Sonja; Zauder, Krešimir (2007)
The Web 2.0, having the user both creating and organizing content, has changed much of how one approaches to and uses the Web. While the concept of user-submitted content is by no means new, user created organizational structure is. The article gives an overview of the organizational means and processes that enable it. To provide the general framework the article gives a short overview of Web 2.0. It then centres on the collaborative tagging process as a central organizational process and means for the Web 2.0 and provides definitions for the Web 2.0 terminology used. After describing the general process, its strengths and weaknesses and pointing out that, while useful, it cannot replace professional indexing tools and library and information science professionals the article goes on to describe collaborative tagging and its specific features in general. Some of the more common services to use collaborative tagging are then described.
Projekt MZOS
ENG